2015
DOI: 10.5194/piahs-366-34-2015
|View full text |Cite
|
Sign up to set email alerts
|

Regional hydrological impacts of climate change: implications for water management in India

Abstract: Abstract. Climate change is most likely to introduce an additional stress to already stressed water systems in developing countries. Climate change is inherently linked with the hydrological cycle and is expected to cause significant alterations in regional water resources systems necessitating measures for adaptation and mitigation. Increasing temperatures, for example, are likely to change precipitation patterns resulting in alterations of regional water availability, evapotranspirative water demand of crops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Past efforts at quantifying the availability of freshwater resources across the country have relied mainly on estimating streamflow trends either through measurements or empirical estimation techniques [ Central Water Commission (CWC), ]. Hydrologic models have also been employed to predict future water availability although this approach, too, relies on streamflow records [ Mondal and Mujumdar , ; Raje et al , ]. Despite an escalation in the spatial extent of water stressed regions across the country, streamflow data remain scarce hindering the growth and development of hydrologic modeling frameworks to provide management solutions [ Mujumdar , ; Rockstrom et al , ; United Nations Environment Programme , ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past efforts at quantifying the availability of freshwater resources across the country have relied mainly on estimating streamflow trends either through measurements or empirical estimation techniques [ Central Water Commission (CWC), ]. Hydrologic models have also been employed to predict future water availability although this approach, too, relies on streamflow records [ Mondal and Mujumdar , ; Raje et al , ]. Despite an escalation in the spatial extent of water stressed regions across the country, streamflow data remain scarce hindering the growth and development of hydrologic modeling frameworks to provide management solutions [ Mujumdar , ; Rockstrom et al , ; United Nations Environment Programme , ].…”
Section: Introductionmentioning
confidence: 99%
“…First, it serves as a stand‐alone baseline to compare estimates based on streamflow data and hydrologic modeling. Second, it provides uncertainty in estimates on freshwater availability that are either overlooked [ CWC , ] or if accounted for are mainly driven by uncertainties from the input climate [ Mondal and Mujumdar , ]. A probabilistic framework enables the quantification of uncertainties from additional sources such as physical characteristics of the region.…”
Section: Introductionmentioning
confidence: 99%
“…In agricultural lands, the amount of water availability influences evaporation rate. Hence, soil moisture [113], rainfall [90] and evaporation variables must be included while assessing water demands for irrigation under climate change [78]. An inter-model comparison identified that not all models were consistent in explaining the present climate in terms of the mean, skewness and asymmetry [31].…”
Section: Ensemble and Multiple Ensemblesmentioning
confidence: 99%
“…Regional and national studies have offered important assessments of the impacts of climate change not only on ecosystems but also on the economy and society. Some of these include the study produced by the Austrian Panel on Climate Change [ 21 ], which consists of a group of some 200 scientists, over a 3 year period followed the methodology of the IPCC and has enabled policy-makers to strengthen Austria's strategy on climate change; the Garnaut Review [ 22 ], Australia's comprehensive review of the impacts of climate change for Australia and an assessment of the contributions that Australia could make globally; the economic assessments made on the impact of climate change on Uganda [ 23 ], which estimated that damage to agriculture, infrastructure, energy and water could total some 2–4% of GDP during the period 2010–2050 and that adaptation costs were high but the costs of inaction significantly higher by some 20–40 times; studies that have provided important methodological advances and analysis based on scenarios for the twenty-first century on the impacts of climate change on the hydrological cycle, such as the one that estimated the effects on water management in India [ 24 ] and the impact of climate change on water resource quantity and quality indicators for a region in Greece [ 25 ]; studies that have estimated the impacts on climate from the bio-geophysical (BGP) and bio-geochemical (BGC) effects of land use change in different regions of the world where close to one-third of the global land surface has already suffered from deforestation and introduction of cropland and pastures [ 26 ]; and studies on ocean acidification and its effect on carbon uptake in different regions of the world due to decreased carbon dioxide solubility and local warming due to large freshwater fluxes, among others [ 27 ].…”
Section: Climate and Development Linkagesmentioning
confidence: 99%